2022
DOI: 10.1007/s00442-021-05081-9
|View full text |Cite
|
Sign up to set email alerts
|

Of mutualism and migration: will interactions with novel ericoid mycorrhizal communities help or hinder northward Rhododendron range shifts?

Abstract: Rapid climate change imperils many small-ranged endemic species as the climate envelopes of their native ranges shift poleward. In addition to abiotic changes, biotic interactions are expected to play a critical role in plant species’ responses. Below-ground interactions are of particular interest given increasing evidence of microbial effects on plant performance and the prevalence of mycorrhizal mutualisms. We used greenhouse mesocosm experiments to investigate how natural northward migration/assisted coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Seeds of ericaceous plants are small with an average length of 1.5 mm and a mean width of 0.5 mm, and they generally have a poor germination rate due to the limited supply of nutrition from the endosperm. In a mesocosm study conducted for determining if novel ErM communities could assist or hamper the shift of northward species of Rhododendron , Mueller et al. (2022) reported that germination rates of R. catawbiense and R. maximum after inoculation with novel soils containing ErM fungi were significantly greater than those of controls (without mycorrhizal fungi) or inoculated with conspecific soils, 75.2% vs. 54.5% for R. catawbiense and 65.7% vs. 54.4% for R. maximum .…”
Section: Ericoid Mycorrhizal Fungi Promote Seed Germination and Rooti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Seeds of ericaceous plants are small with an average length of 1.5 mm and a mean width of 0.5 mm, and they generally have a poor germination rate due to the limited supply of nutrition from the endosperm. In a mesocosm study conducted for determining if novel ErM communities could assist or hamper the shift of northward species of Rhododendron , Mueller et al. (2022) reported that germination rates of R. catawbiense and R. maximum after inoculation with novel soils containing ErM fungi were significantly greater than those of controls (without mycorrhizal fungi) or inoculated with conspecific soils, 75.2% vs. 54.5% for R. catawbiense and 65.7% vs. 54.4% for R. maximum .…”
Section: Ericoid Mycorrhizal Fungi Promote Seed Germination and Rooti...mentioning
confidence: 99%
“…Ericoid mycorrhizal fungi improve seed germination and rooting of cuttings Mueller et al (2022). reported that germination rates of R. catawbiense and R. maximum after inoculation with novel soils containing ErM fungi were significantly greater than those of controls (without mycorrhizal fungi) or inoculated with conspecific soils, 75.2% vs. 54.5% for R. catawbiense and 65.7% vs. 54.4% for R. maximum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Allee effects may occur if animal pollinators are less likely to visit more isolated individuals or low-density populations, such as at a range edge, which could limit the seed set [ 176 , 300 , 301 , 302 ]. Changes in the density or composition of root mutualists, such as mycorrhizal fungi, can also affect range shifts [ 260 , 303 , 304 , 305 ]. For example, reduced densities of mycorrhizal mutualists of native plant species have been shown to enhance the population growth of invading non-native plant species [ 306 ].…”
Section: Phenotype–environment Matchingmentioning
confidence: 99%
“…Ultimately, climate change will not only affect plants via direct effects on the abiotic dimensions of the ecological niche, but it will also affect the organisms with which plants have mutualistic and antagonistic interactions, likely causing changes in their population densities and ranges. Complex decoupling of the distributions of plants from their mutualists and antagonists could inhibit or promote range shifts in ways that depend on the species’ ecological strategy and unavoidable trade-offs across life stages [ 263 , 304 , 305 ].…”
Section: Phenotype–environment Matchingmentioning
confidence: 99%